Relationships between muscle sympathetic nerve activity and novel indices of arterial stiffness using single oscillometric cuff in patients with hypertension. Issue 10 (19th May 2022) - Sugimoto, Hiroyuki; Hamaoka, Takuto; Murai, Hisayoshi; Hirai, Tadayuki; Mukai, Yusuke; Kusayama, Takashi; Takashima, Shinichiro; Kato, Takeshi; Takata, Shigeo; Usui, Soichiro; Sakata, Kenji; Kawashiri, Masa‐Aki; et al.
Abstract: The arterial velocity pulse index (AVI) and arterial pressure‐volume index (API) have been proposed as new arterial stiffness indices that can be measured using an oscillometric cuff. Sympathetic nerve activity (SNA) contributes to arterial stiffness via increasing vascular smooth muscle tone. However, the associations between SNA and the AVI or API are not understood. The purpose of this study was to evaluate the relationships between muscle sympathetic nerve activity (MSNA) and the AVI or API in healthy individuals and patients with hypertension (HT). Forty healthy individuals (40.1 ± 15.2 years, 8 females) (healthy group) and 40 patients with HT (60.2 ± 13.6, 18 females) (HT group) were included in this study. The AVI, API, MSNA, beat‐by‐beat blood pressure, and heart rate were recorded simultaneously. The AVI and API were higher in the HT group than in the healthy group (AVI, 26.1 ± 7.6 vs. 16.5 ± 4.0, p  < 0.001; API, 31.2 ± 8.6 vs. 25.5 ± 7.2, p  = 0.002). MSNA in the HT group was also higher than in the healthy group ( p  < 0.001). MSNA was correlated with the AVI, but not with the API, in both the healthy group ( R  = 0.52, p  = 0.001) and HT group ( R  = 0.57, p  < 0.001). MSNA was independently correlated with the AVI in multivariate analysis ( ß  = 0.34, p  = 0.001). In conclusion, AVI, obtained by a simple and less user‐dependent method, was related to the MSNA in healthy individuals and patients with HT. Abstract : Arterial velocity pulse index (AVI) is a novel arterial stiffness index that can be measured by a single oscillometric cuff. We found that AVI was significantly correlated with muscle sympathetic nerve activity (MSNA) in both healthy subjects and patients with hypertension, which is likely related to the influence of MSNA on arterial wave reflection.